Solve equation for x:

a) `ln(x^2-1)=3`

### 1 Answer | Add Yours

If you have more than one question you need to make separate posts.

To solve this equation, we need to change the equation from logarithmic to exponential form.

`ln(x^2-1)=3`

`x^2-1=e^3` move 1 to other side

`x^2=1+e^3` take square roots

`x=+-sqrt{1+e^3}`

For both potential solutions, when we substitute back into the original equation, we get valid solutions.

**The solutions of the equation are `x=+-sqrt{1+e^3}` .**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes